Pengembangan Pariwisata Budaya Berbasis Kearifan Lokal Mandullu’u’ Tonna Dan Pemberdayaan Masyarakat Di Kabupaten Kepulauan Talaud, Sulawesi Utara - Efraim Laluas; Helni Desty Yanice Lagarense; Ruslani (Jurnal Ilmu Pariwisata, 2025)
This study examines the potential and development strategies of cultural tourism based on local wisdom through the Madulu’u’tonna Festival in the Talaud Islands Regency, North Sulawesi Province. Despite being classified as a less-developed region, Talaud possesses rich and distinctive cultural traditions that offer significant potential as alternative tourism attractions. This research adopts a qualitative method with an ethnographic approach, employing field observations, in-depth interviews, and Focus Group Discussions (FGDs). Data analysis is guided by the 4A framework—Attraction, Accessibility, Amenity, and Ancillary—to assess opportunities and constraints in developing the Madulu’u’tonna Festival as a cultural tourism asset. The findings indicate that the festival embodies profound spiritual, social, and economic values for the local community and demonstrates strong potential to evolve into a flagship cultural tourism event. Nevertheless, inadequate infrastructure and limited promotional capacity remain major challenges. The novelty of this study lies in its integrative and holistic approach, which links local wisdom with community-based tourism development while proposing a cultural preservation model that prioritizes local empowerment and the strengthening of regional cultural identity.